Fresh Rumen Liquid Inoculant Enhances the Rumen Microbial Community Establishment in Pre-weaned Dairy Calves - Huuki, Hanna; Ahvenjärvi, Seppo; Lidauer, Paula; Popova, Milka; Vilkki, Johanna; Vanhatalo, Aila; Tapio, Ilma (Frontiers in Microbiology, 2022)
The development of functional rumen in calves involves a complex interplay between the host and host-related microbiome. Attempts to modulate rumen microbial community establishment, therefore, may have an impact on weaning success, calf health, and animal performance later in life. In this experiment, we aimed to elucidate how rumen liquid inoculum from an adult cow, provided to calves during the pre-weaning period, will influence establishment of rumen bacterial, archaeal, fungal, and ciliate protozoan communities in monozygotic twin-calves (n=6 pairs). Calves were divided into treatment (T) and control (C) groups, where T-group received fresh rumen liquid as oral inoculum until eight weeks of age. C-group was not inoculated. Rumen microbial community composition was determined using 16S and 18S rRNA gene as well as ITS1 amplicon sequencing. Animal weight gain and feed intake were monitored throughout the experiment. T-group had numerically higher solid feed intake and significantly better weekly weight gain, but the differences could not be associated with rumen fermentation characteristics. The inoculum in T-group stimulated an earlier establishment of several bacterial taxa, related to solid feed digestion and mature rumen, e.g. Fibrobacter and Prevotella. It also increased the archaeal OTU diversity but did not affect the archaeal quantity. Due to inoculum, ciliate protozoa inhabited the rumen of T-group calves starting from week two, while C-group remained defaunated until six weeks of age. Differences in ciliate protozoa composition between the groups were observed at 8 weeks of age, with Eremoplastron dilobum being the most abundant species in C and Isotricha sp., in T-group. The alpha diversity of ruminal fungi reduced with age, and fungal community establishment was influenced by changing diet and, potentially, interaction with other rumen microorganisms. Our results indicate that adult cow rumen liquid inoculum enhanced the maturation of bacterial and archaeal communities in pre-weaning calves rumen whereas its effect on eukaryotic communities was less clear and requires further investigations.